2017
DOI: 10.1534/genetics.116.197293
|View full text |Cite
|
Sign up to set email alerts
|

Potential Nematode Alarm Pheromone Induces Acute Avoidance in Caenorhabditis elegans

Abstract: It is crucial for animal survival to detect dangers such as predators. A good indicator of dangers is injury of conspecifics. Here we show that fluids released from injured conspecifics invoke acute avoidance in both free-living and parasitic nematodes. avoids extracts from closely related nematode species but not fruit fly larvae. The worm extracts have no impact on animal lifespan, suggesting that the worm extract may function as an alarm instead of inflicting physical harm. Avoidance of the worm extract req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…It is therefore conserved throughout the animal kingdom 41,42 . For example, in the nematode Caenorhabditis elegans (C. elegans), stress linked to environmental conditions can impact food preferences when they are coupled with odorants 43 as well as with alarm pheromones and predator scents 44,45 . Interestingly, this worm modality is dependent on a specific olfactory subsystem composed of a pair of amphid wing cells of type C 46 (AWC).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore conserved throughout the animal kingdom 41,42 . For example, in the nematode Caenorhabditis elegans (C. elegans), stress linked to environmental conditions can impact food preferences when they are coupled with odorants 43 as well as with alarm pheromones and predator scents 44,45 . Interestingly, this worm modality is dependent on a specific olfactory subsystem composed of a pair of amphid wing cells of type C 46 (AWC).…”
Section: Discussionmentioning
confidence: 99%
“…the observed suppression of nematode migration towards roots, Therefore, we tested a series of combinations of ascr#18, which is directly excreted by the nematodes, and its most abundant plant metabolite, ascr#9, in a previously described quantitative chemotaxis population assay 38 (Fig. 5c).…”
Section: Resultsmentioning
confidence: 99%
“…Worms that remained in the center 0.5-cm-wide strip were not counted. The attraction index was calculated as (A -B/A + B), where A and B denote numbers of nematodes on the test solution side and mock solution side, respectively 38 . All experiments were independently performed four times.…”
Section: Methodsmentioning
confidence: 99%
“…Worms appear to avoid other putative pheromone components. Zhou et al found that the internal fluid from injured worms elicited repulsive behavior in adult hermaphrodites via the ASI and ASK chemosensory neurons (Zhou et al, 2017). The group also found that this internal fluid did not affect the lifespan of worms, suggesting that this fluid acts as not a harmful repellent chemical but as an alarm pheromone (Zhou et al, 2017).…”
Section: Avoidance Behavior To Other Pheromonesmentioning
confidence: 99%
“…Zhou et al found that the internal fluid from injured worms elicited repulsive behavior in adult hermaphrodites via the ASI and ASK chemosensory neurons (Zhou et al, 2017). The group also found that this internal fluid did not affect the lifespan of worms, suggesting that this fluid acts as not a harmful repellent chemical but as an alarm pheromone (Zhou et al, 2017). This potential pheromone was none of the known ascarosides but comprised at least three nonvolatile components (Zhou et al, 2017).…”
Section: Avoidance Behavior To Other Pheromonesmentioning
confidence: 99%